Antena Mikrostrip Rectangular Patch dengan Inset-Feed dan Array Frekuensi 2.1 Ghz untuk Memperkuat Jaringan 5G - Desti Putri, Rahayu; Yulindon, Yulindon; Nawi, Nasrul (Journal of Comprehensive Science, 2025)
This study proposes the design of an antenna that works at the frequency of 2.1 GHz used for fifth-generation communication systems. The antenna is designed with FR-4 Epoxy substrate which has the specification of dielectric constant = 4.3, substrate thickness = 1.6 mm. FR-4 Epoxy substrate was chosen because it has a small dielectric constant value, so antenna losses can be reduced. The antenna is designed to have high gain and directional radiation patterns by the inset feed method and array method. The antennas that have been added with the inset feed method and array method have a return loss area of -47,785 dB, VSWR 1,008, and a gain of 6,393 dB at a frequency of 2.1 GHz. After using the inset feed method, the return loss value was successfully reduced to 95.48%, the bandwidth increased by 4.06% and by using the array method, the gain value increased by up to 95.93% compared to the single-element antenna. This research can be used as a recommendation for the design of receiver antennas in 5G communication systems.